Endoplasmic reticulum targeting fluorescent probes to image mobile Zn2+. Issue 47 (22nd October 2019) - Fang, Le; Trigiante, Giuseppe; Crespo-Otero, Rachel; Hawes, Chris S.; Philpott, Michael P.; Jones, Christopher R.; Watkinson, Michael
Abstract : Two endoplasmic reticulum (ER) targeting probes were developed to image mobile Zn 2+ to help understand Zn 2+ related biological processes in the ER. Abstract : Zn 2+ plays an important role in the normal function of the endoplasmic reticulum (ER) and its deficiency can cause ER stress, which is related to a wide range of diseases. In order to provide tools to better understand the role of mobile Zn 2+ in ER processes, the first custom designed ER-localised fluorescent Zn 2+ probes have been developed through the introduction of a cyclohexyl sulfonylurea as an ER-targeting unit with different Zn 2+ receptors. Experiments in vitro and in cellulo show that both probes have a good fluorescence switch on response to Zn 2+, high selectivity over other cations, low toxicity, ER-specific targeting ability and are efficacious imaging agents for mobile Zn 2+ in four different cell lines. Probe 9 has been used to detect mobile Zn 2+ changes under ER stress induced by both tunicamycin or thapsigargin, which indicates that the new probes should allow a better understanding of the mechanisms cells use to respond to dysfunction of zinc homeostasis in the ER and its role in the initiation and progression of diseases to be developed.